Comparison of Ethnomathematical Concepts in Mosque Architecture in North Sumatra: A Case Study of Al-Mashun Grand Mosque and Al-Osmani Grand - Siti Jubaidah; Lola Mandasari (Universitas Negeri Surabaya, 2025)
Indonesian mosque architecture in North Sumatra is full of ornaments and shapes that are not just of visual interest, but also philosophically and mathematically very relevant. Nevertheless, very little research exists that specifically compares the application of ethnomathematical concepts in two very old mosques, the Al-Mashun Grand Mosque and the Al-Osmani Grand Mosque. Indeed, these two mosques are a peculiar combination of domestic culture and external influences, as expressed by the building's form and decoration. This research evaluated architectural aspects with the help of indicators like geometric shapes (circle, triangle, square, rhombus), three-dimensional objects (block, cube, tube, hemisphere), and geometric transformations (reflection, translation, rotation). This research aims to: (1) establish the application of ethnomathematical concepts to Al-Mashun Grand Mosque architecture; (2) to establish the application of ethnomathematical concepts to Al-Osmani Grand Mosque architecture; and (3) compare the results of the application of the concept in the two mosques. This study applies qualitative descriptive research with the case study approach, comparing data using comparative descriptive analysis of field observation, visual documentation, and reading study. The results of this study show that Al-Mashun Grand Mosque emphasizes symmetrical octagonal buildings and intricate ornaments in the Middle Eastern style of design, while Al-Osmani Grand Mosque emphasizes rectangular buildings and Malay ornamentations. Both employ geometric transformations that enhance harmony, order, and cultural identity. These findings illustrate that Islamic architecture serves not merely as a space for worship but also as a conduit for integrating cultural values with mathematical principles.